RESPONSE OF STREAMS AND SUPRAPERMAFROST WATERS OF THE ANADYR LOWLAND TO ATMOSPHERIC PRESSURE DROP - О.Д. Трегубов; Б.И. Гарцман; В.В. Шамов; Л.С. Лебедева; А.М. Тарбеева (Для почтовых отправлений: 199155 Санкт-Петербург, а/я 136, Редакция журнала «Гидросфера. Опасные процессы и явления» / For mail: 199155 St. Petersburg, PO Box 136 Editorial Board of the «Hydrosphere. Hazardous processes and phenomena»., 2021)
The article presents the results of a study of water supply sources and the daily flow regime of rivers and streams of the Anadyr lowland in the low-water period of 2019. Regarding the field materials, the problem of the impact of atmospheric pressure surges on the water-physical properties of peat soils and the runoff regime of small rivers in the cryolithozone lowlands is considered. It was found that the daily atmospheric pressure drop with an amplitude of 1.2 kPa in the Ugolnaya-Dionisiya River watershead, located within the Anadyr Lowland in Chukotka, led to a synchronous decrease and then an increase in the level of suprapermafrost and river waters by 2.5– 7.8 cm. The water-physical properties of peat soils are described, the mechanism of the influence of atmospheric pressure on the tundra soils moisture capacity and the small rivers runoff during the summer dry season is proposed. The geocryological, hydrogeological and hydrological conditions necessary for the manifestation of discovered effect are considered. The known mechanical properties of the tundra peat cover and the water-physical properties of the organogenic horizon of tundra soils made allow to propose a hypothesis of the effect of atmospheric pressure on the level of suprapermafrost waters by changing the moisture capacity of peat during its plastic-elastic deformation. The condition for a positive reaction of suprapermafrost and river runoff to fluctuations in atmospheric pressure are: the bedding of the groundwater table in contact with the peat horizon; incomplete moisture capacity of the organogenic soil horizon; predominant feeding of the river by suprapermafrost waters and the presence of an extensive drainage network. It seems promising to further study the atmospheric baric effects of baroeffects in the underground and surface waters of the lowlands of the permafrost zone, as well as in the bog landscapes of more southern latitudes, where there are conditions for their manifestation. In the landscape conditions of the Anadyr Lowland, ...